Criminal narrative experience: relating emotions to offence narrative roles during crime commission - Ioannou, Maria (International journal of offender therapy and comparative criminology, 2017)
A neglected area of research within criminality has been that of the experience of the offence for the offender. The present study investigates the emotions and narrative roles that are experienced by an offender while committing a broad range of crimes and proposes a model of criminal narrative experience (CNE). Hypotheses were derived from the circumplex of emotions, Frye, narrative theory, and its link with investigative psychology. The analysis was based on 120 cases. Convicted for a variety of crimes, incarcerated criminals were interviewed and the data were subjected to smallest space analysis (SSA). Four themes of CNE were identified: Elated Hero, Calm Professional, Distressed Revenger, and Depressed Victim in line with the recent theoretical framework posited for narrative offence roles. The theoretical implications for understanding crime on the basis of the CNE as well as practical implications are discussed.